Gap junctions between interneurons are required for normal spatial coding in the hippocampus and short-term spatial memory. - Allen, K; Fuchs, E; Jaschonek, H; Bannerman, D; Monyer, H (2011)
Gap junctions containing connexin 36 electrically couple interneurons in many brain regions and synchronize their activity. We used connexin-36 knock-out mice (Cx36(-/-)) to study the importance of electrical coupling between interneurons for spatial coding in the hippocampus and for different forms of hippocampus-dependent spatial memory. Recordings in behaving mice revealed that the spatial selectivity of hippocampal pyramidal neurons was reduced and less stable in Cx36(-/-) mice. Altered network activity was reflected in slower theta oscillations in the mutants. Temporal coding, assessed by determining the presence and characteristics of theta phase precession, had different dynamics in Cx36(-/-) mice compared with controls. At the behavioral level, Cx36(-/-) mice displayed impaired short-term spatial memory but normal spatial reference memory. These results highlight the functional role of electrically coupled interneurons for spatial coding and cognition. Moreover, they suggest that the precise spatial selectivity of place cells is not essential for normal performance on spatial tasks assessing associative long-term memory.